Epidemiological Trends in Alopecia Areata at the Global, Regional, and National Levels - Wang, Haifeng; Pan, Lifang; Wu, Yanfeng (Frontiers in Immunology, 2022)
Background: No comprehensive studies have been published on the global burden of alopecia areata since 2010. Objective: We aimed to measure the global, regional, and national incidence of alopecia areata and disability-adjusted life-years (DALYs) by age, sex, and socio-demographic index (SDI) value from 1990 to 2019. Methods: Data were extracted from the Global Burden of Disease Study 2019. Estimated annual percentage changes (EAPCs) were calculated to quantify temporal trends in the age-standardized rates of alopecia areata incidence and DALYs. The correlations between EAPCs in the age-standardized rates and SDI values were also analyzed. Results: From 1990 to 2019, the alopecia areata incidence number and the associated number of DALYs increased globally by 49.14%, and 49.51%, respectively. The global age-standardized incidence rate decreased (EAPC, −0.13; 95% confidence interval [CI], −0.13 to −0.12) and the age-standardized DALY rate showed a downward trend (EAPC, −0.12; 95% CI, −0.13 to −0.11). The largest increases in the age-standardized incidence rate and age-standardized DALY rate were observed in Low SDI quintile and Western Sub-Saharan Africa regions. The regions with the greatest changes in the incidence of alopecia areata were Central Sub-Saharan Africa and Western Sub-Saharan Africa. The three countries with the largest increases in alopecia areata incidence from 1990 to 2019 were Kuwait (EAPC, 0.15), South Sudan (EAPC, 0.12), and Nigeria (EAPC, 0.11). The age-standardized incidence rate was higher in females than in males. Conclusion: Globally, both the age-standardized incidence rate and age-standardized DALY rate of alopecia areata showed decreasing trends. Future preventive strategies should focus on low-income countries, Central Sub-Saharan Africa, Western Sub-Saharan Africa, Kuwait, South Sudan, Nigeria.